Challenges of Prose Fiction Writing in Uganda: A Case Study of Kanungu District in Western Uganda. - Kabagyenyi, Maurine (Kabale University, 2024)
The purpose of this study was to find out the challenges faced by prose fiction writers in Uganda. The study was guided by the following objectives; to identify the relevance of short stories in Uganda, and to identify the challenges faced by prose fiction writers in Uganda